You Don't Know JS : ES6 and Beyond - Simpson, Kyle; St. Laurent, Simon; MacDonald, Brian (Sebastopol, CA ; Mumbai : O'Reilly Media ; Shroff Publishers and Distributors Pvt. Ltd., 2015)
No matter how much experience you have with JavaScript, odds are you don't fully understand the language. As part of the "You Don't Know JS" series, this compact guide focuses on new features available in ECMAScript 6 (ES6), the latest version of the standard upon which JavaScript is built
CSE
Hay Trade International
Keywords: JavaScript (Computer program language).; Computer science; JavaScript (Computer program language)